(untitled) (Research, Society and Development, 2022)
The development of new energy technologies is crucial for climate stability and planet security. The growing energy demand has driven several researches aiming increase the supply of electricity, nationally and globally. The depletion of some energy resources makes it necessary to expand the forms of energy generation, materials and technologies used. Given this scenario, polymeric photovoltaic solar cells offer a potential route for implantation of large-scale solar energy once they enable cost reduction, using materials abundant in nature and low-cost production technologies. Polymeric solar cells, composed of organic materials, can be used both as an alternative in energy production. In this research work, a study was carried out on the production process and working mechanisms of polymeric solar cells. The studied devices were produced by a blade coating method, with active layer composed of hybrid films polymer:fulerene based on poly(3-hexylthiophene-2,5-diyl) (P3HT):[6,6]-phenyl-C61- butyric acid methyl ester (PCBM). The evaluated photovoltaic parameters presented small dispersion values, suggesting that the employed method proved to be efficient in the fabrication of the devices. The energy conversion efficiency of the photovoltaic device with the best performance was estimated to be around 3.12%.